ANALYZING CUSTOMERS PAYMENT CHOICE AT PT. BANK NEGARA INDONESIA (PERSERO) TBK. IN MANADO - Hermanto, Wulandari (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
The changing of technology development in the payment system create various payment facilities of electronic payment (e-payment) namely internet banking, mobile banking, DOKU wallet and RTGS. These payment facilities make the people have a variety of payment choice that make people easier in doing transaction process. That is why this research needed to know how the people make the decision of payment choice. Theories that are supporting this research are motivation, trusting beliefs and perception. The population of this research is all customers of BNI Manado, and the sample is 10 respondents which take from the different of occupation and age. This research used qualitative analysis, using the interview and observation techniques. The findings of results and conclusions are most of respondents prefer to use cash payment rather than e-payment. This is caused by the lack of motivation and information toward customers of bank itself. To fix this problem, bank must improve the motivation and give better information for customers in order to make customers know how to use the payment facilities. Keywords: payment choice, consumer behavior, payment system, cash, e-payment, motivation, trusting beliefs, perception